Extracellular vesicles derived from SARS-CoV-2 M-protein-induced triple negative breast cancer cells promoted the ability of tissue stem cells supporting cancer progression - Nguyen, Hoai-Nga Thi; Vuong, Cat-Khanh; Fukushige, Mizuho; Usuda, Momoko; Takagi, Liora Kaho; Yamashita, Toshiharu; Obata-Yasuoka, Mana; Hamada, Hiromi; Osaka, Motoo; Tsukada, Toru; Hiramatsu, Yuji; Ohneda, Osamu (Frontiers in Oncology, 2024)
SARS-CoV2 infection increases the risk of worse outcomes in cancer patients, including those with breast cancer. Our previous study reported that the SARS-CoV-2 membrane protein (M-protein) promotes the malignant transformation of triple-negative breast cancer cells (triple-negative BCC). In the present study, the effects of M-protein on the ability of extracellular vesicles (EV) derived from triple-negative BCC to regulate the functions of tissue stem cells facilitating the tumor microenvironment were examined. Our results showed that EV derived from M-protein-induced triple-negative BCC (MpEV) significantly induced the paracrine effects of adipose tissue-derived mesenchymal stem cells (ATMSC) on non-aggressive BCC, promoting the migration, stemness phenotypes, and in vivo metastasis of BCC, which is related to PGE2/IL1 signaling pathways, in comparison to EV derived from normal triple-negative BCC (nEV). In addition to ATMSC, the effects of MpEV on endothelial progenitor cells (EPC), another type of tissue stem cells, were examined. Our data suggested that EPC uptaking MpEV acquired a tumor endothelial cell-like phenotype, with increasing angiogenesis and the ability to support the aggressiveness and metastasis of non-aggressive BCC. Taken together, our findings suggest the role of SARS-CoV-2 M-protein in altering the cellular communication between cancer cells and other non-cancer cells inside the tumor microenvironment via EV. Specifically, M-proteins induced the ability of EV derived from triple-negative BCC to promote the functions of non-cancer cells, such as tissue stem cells, in tumorigenesis.